Making it right? Social norms, hand writing and cognitive skills - Raphael Guber (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Forcing a left-handed child to use the right hand for writing was long common practice in the Western world. Although it is rare now in these societies, it is still highly prevalent in developing countries and across various cultures. Forced right-hand writing is a rare early childhood intervention that was performed on a large scale and throughout history. In this paper we investigate how this intervention affected educational outcomes and cognitive skills in German adults in the mid and long run. To identify causal effects we use the decline of the right-hand writing norm across cohorts in a difference-in-differences first stage, where right-handers serve as counterfactual group. While OLS estimates indicate that treated individuals obtained more years of education and better math grades (compared to all others), our 2SLS coefficients suggest zero or negative effects for educational outcomes, and strong negative effects on cognitive skills. These findings are in line with brain scans that show reduced gray matter in the putamen of switched German adults, which is responsible for motor skills and cognitive functioning.
Keywords: J24; I10; I21; 330